Evaluation of optical properties of different types of contact lenses - Pereira, Clara (2013)
The main objective of this work was to attain a deeper knowledge of contact lenses (CL) optical properties and to understand the influence of CL power on other properties which can affect the optical performance and compromise the ocular physiology.